ByzRev 06.2024.042: Rustam Shukurov, Византия и Азия.: Гибель цивилизации [Byzantium and Asia: The Demise of a Civilization]. Saint Petersburg: Наука 2023. - Parpulov, Georgi (The Byzantine Review, 2024)
Rustam Shukurov, Византия и Азия. Гибель цивилизации [Byzantium and Asia: The Demise of a Civilization]. Saint Petersburg: Наука 2023. 375 pp. – ISBN 978-5-02-040284-3